Modelling of hydrogen permeation experiments in iron alloys: Characterization of the accessible parameters – Part II – The exit side. (1st February 2018) - Vecchi, Lorenzo; Simillion, Hans; Montoya, Rodrigo; Van Laethem, Dries; Van den Eeckhout, Emilie; Verbeken, Kim; Terryn, Herman; Deconinck, Johan; Van Ingelgem, Yves
Abstract: Electrochemical permeation tests are used to investigate the diffusion and trapping effects of hydrogen in a metal. For a quantitative and reliable evaluation of these features, the development of a numerical model is required. In the first paper of this series, we developed a model describing the hydrogen transport process in the Devanathan-Stachurski cell and evaluated the influence of the entry interface on the experimental results. Although many models have already been proposed for the description of the hydrogen diffusion in the Devanathan-Stachurski cell, none of them is including the simulations of the anodic side of the cell. In this paper, we present a new model representing the Devanathan-Stachurski cell. With this model, we are able to make a sensitivity analysis of all the parameters that play a role during the hydrogen diffusion process in iron alloys, comprising the adsorption, absorption, diffusion and desorption processes that the hydrogen undertakes in the sample mounted in the Devanathan-Stachurski cell. In particular, we found that the common assumption of constant zero concentration at exit side broadly accepted by researchers may not always reflect the real situation and the evaluation of the desorption process as often used today might be oversimplified. Certainly, the complexity of the desorption/oxidation is of high degree when Pd coating is not applied at the exit side. Consequently, the effect of the anodic electrolyte and the surface state at exit side should be considered as a significant element affecting the experimental results.